1997
DOI: 10.1200/jco.1997.15.5.1803
|View full text |Cite
|
Sign up to set email alerts
|

Second cancer risk in hairy cell leukemia: analysis of 350 patients.

Abstract: Among 350 patients with HCL, there was an increase in the number of second cancers; however, it did not reach statistical significance and was not associated with therapy. The incidence of lymphoid neoplasms was significantly higher than expected. Survival since the advent of effective systemic therapy was excellent, although excess mortality was still observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 13 publications
3
63
2
3
Order By: Relevance
“…[20][21][22] Two reports 20,21 suggested an increased incidence of second malignancy, the largest however 22 could not support this suspicion. In our small series, eight pts (18%) suffered from additional cancer at start of 2-CdA treatment, six of them died without any evidence of active or residual HCL, two are in CCR.…”
Section: Discussionmentioning
confidence: 73%
“…[20][21][22] Two reports 20,21 suggested an increased incidence of second malignancy, the largest however 22 could not support this suspicion. In our small series, eight pts (18%) suffered from additional cancer at start of 2-CdA treatment, six of them died without any evidence of active or residual HCL, two are in CCR.…”
Section: Discussionmentioning
confidence: 73%
“…24 In the present data, 16 patients had herpes infection, and 18 developed a second malignancy (7.5%), a figure slightly lower than the 10% rate reported by Ribeiro et al 11 and Finn et al 17 Recently the Italian group reported data on 1022 patients treated by splenectomy and/or IFN, and showed that the cumulative risk of development of a second cancer was 5%, 10%, and 14% at 5, 10, and 15 years, respectively, but not associated with a significant increased risk of additional second malignancies. 25 Kurzrock et al 20 demonstrated an increase in the number of second cancers, however it was not associated with therapy. On the contrary, Au et al 26 reported an increased relative risk of second cancer among men of 2.91 (P Ͻ 0.001) related to immunosuppres-sion due to HCL or its treatment.…”
Section: Figurementioning
confidence: 99%
“…However, mortality was greater in patients with hairy cell leukemia than in the general population in a retrospective analysis of 350 patients, primarily because of disease-related infection and second malignancies. 20 Treatment with DCF was usually well tolerated. Myelosuppression was the most frequent side-effect associated with the use of DCF.…”
Section: Figurementioning
confidence: 99%
“…8 The occurrence of second neoplasms in patients with HCL is a well-known fact. [9][10][11][12][13][14][15] Among them, non-Hodgkin's lym- phomas are the most frequently hematological malignancies reported. 10,15,16 The association of HCL and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is considered to be exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Among them, non-Hodgkin's lym- phomas are the most frequently hematological malignancies reported. 10,15,16 The association of HCL and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is considered to be exceedingly rare. Thus, in an extensive computer-assisted search of the literature, only one case of transformation of CLL/SLL into HCL, 17 one case of HCL diagnosed years after the diagnosis of CLL/SLL, 18 and some cases of lymphoproliferative disorders with intermediate features between HCL and CLL/SLL [19][20][21] have been reported.…”
Section: Introductionmentioning
confidence: 99%